Modelo de programación de producción en la línea textil de la empresa Kromia S.A.S (2020)
In the studied company, which belongs to the textile industry, a flexible hybrid flow shop type production configuration is evident, in which is presented a series of characteristics that excludes the production programming of the standard models. Due to NP-Hard nature of the problem shown in the company Kromia S.A.S, it has been necessary to use the programming methodology based on genetic algorithms, as a scheduling tool, aimed at minimazing makespan and the amount of late jobs; this model is developed taking into account the complexities of the industry, among which are the capacity of parallel machines, delivery times, linear process flow and stage skipping. The methodology developed generates good results compared to real company scenarios.